(untitled) (Scientific journal of the Fergana State University, 2024)
The article contains a number of comments and examples about the scope of application of heat-preserving materials, the advantages of the practical use of ceramic products, what aspects should be paid attention to when choosing heat-insulating materials, fire-resistant components, the type, classification and properties of heat-insulating materials, describes a number of chemical studies conducted on trends in the development of fire retardant coatings.